Review of Jacek BOCHEŃSKI, Divine Julius. Or, How to Become a God in Four Easy Steps - Cappello, Orazio (Ciceroniana On Line, 2024)
Review of Jacek BOCHEŃSKI, Divine Julius. Or, How to Become a God in Four Easy Steps, Trans. T. Pinch, Mondrala Press, Luxembourg 2022, 210 pp., ISBN 9789998793774.